Konsep Religiosity Index dalam Perspektif Hadis Tarbawi dan Relevansinya terhadap Pendidikan Islam - Karimah Karimah; Lisa Wahyuni Lubis; Neisya Ardana Lubis; Dwi Meutia Hasni (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This study examines the relevance of the religiosity index to Islamic education from the perspective of Tarbawi hadith. The study is motivated by the tendency of religiosity research to focus primarily on ritual and spiritual dimensions, while social, moral, and educational dimensions have not been sufficiently integrated within the framework of Tarbawi hadith. The purpose of this study is to analyze the concept of the religiosity index based on the hadith of Prophet Muhammad ﷺ and to explain its relevance to Islamic education. This study employs a qualitative approach using library research by reviewing hadith literature, books, and scholarly journals related to religiosity and Islamic education. Hadith analysis was conducted thematically by classifying hadith based on educational values, including morality, social awareness, discipline, responsibility, patience, and tolerance. The findings indicate that, from the perspective of Tarbawi hadith, the religiosity index is multidimensional, encompassing aspects of faith, worship, morality, social interaction, discipline, responsibility, tolerance, and patience. These values are highly relevant to the objectives of Islamic education in shaping students’ religious character. Furthermore, the religiosity index can function as an evaluative instrument to measure the success of religious character development in educational settings. The findings also imply that Islamic education should emphasize a balanced integration of spiritual, moral, and social dimensions to comprehensively develop students’ religious character.